Treatment of Acute Graft-versus-Host Disease in Liver Transplant Recipients - Edward Kim; Alina Adeel; Adel Bozorgzadeh; Shinya Amano; Curtis T. Barry; Jennifer S. Daly; Deepika Devuni; Zendee Elaba; Laura Houk; Paulo N. Martins; Babak Movahedi; Muthalagu Ramanathan; et al. (Case Reports in Transplantation)
Acute graft-versus-host disease (aGvHD) is a rare complication of liver transplantation associated with high morbidity and mortality. Death typically occurs due to complications related to severe infection, shock, and multiorgan failure. The clinical presentation involves dysfunction of multiple organ systems with overlapping symptoms that often results in a diagnostic delay. As there are a limited number of cases reported in the literature, there are no clear guidelines for treatment. Many different therapeutic measures have been utilized that target various immune system pathways, but steroids remain the first line of therapy. We report on two patients who developed aGvHD after liver transplantation who were treated with ruxolitinib, a novel Janus kinase 1/2 (JAK) inhibitor that has been shown to improve outcomes in steroid refractory cases of aGvHD after allogenic hematopoietic stem cell transplantation. We reviewed the literature to discuss various therapeutic options currently available for aGvHD after liver transplantation.